PENERAPAN METODE MINDMAPPING DENGAN APLIKASI IMINDMAP UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI WAQAF, HIBAH, SHODAQAH, DAN HADIAH DI MA AN-NUR BULULAWANG - Tathaka Wisada Putra Tulungagung; Anwar Sa’dullah; Ach Faisol (VICRATINA, 2019)
In today's era, technology has increased so rapidly that there needs to be a more effective and efficient learning method. The suitable method is the mindmapping method using the Imindmap application. This research will be examined at MA An-nur Bululawang in the X-IAG class. The researcher carried out there because there were many problems in class X-IAG such as lazy learning, lack of motivation, etc. which resulted in student learning outcomes declining. Therefore, there is a need for research to create a good classroom atmosphere. With this research, hopefully students can improve student learning outcomes. The desired results from researchers are looking at improving student learning outcomes.